GEOMECHANICAL ANALYSIS IN CONNECTION WITH PORE PRESSURE AT CEPU AND SURROUNDING REGIONS, NORTH EAST JAVA BASIN - MARDHIKA RUBIANTO (NIM: 22013021), ZAIN
The purpose of the study is to integrate geological data, wireline log data, pressure data and well final report contained in the wells in the North East Java Basin especially Cepu area and its surrounding. The data are used as input in predicting pore pressure using the eaton methodÃ‚Â’s and building 1D geomechanics modeling. Initial hypothesis is to determine whether a horizontal stress is the main stress regime and also to know the relationship between pressure and stress regime in the study area. The results of this study indicate that the maximum horizontal stress orientation is NE - SW direction . The stress regime is a strike slip and stress gradient in the North East Java Basin especially in condition of normal pressure zone and overpressure zone is homogeneous in all wells. Mohr Coulomb analysis shows that fault with NNE - SSW orientation and ENE Ã‚Â– WSW (oblique to the direction of maximum horizontal stress) is critically stressed. In addition, pore pressures in all zones indicate that the difference between the maximum horizontal stress and minimum horizontal stress is almost touching the failure line (μ=0.6) so that the NNE - SSW faults and ENE - WSW are critical. Changes in reservoir pressure (pore pressure) will cause fault reactivation. Of the 17 wells, only three wells show stable stress (stress difference under the failure line) both of them are in the normal pressure zone and overpressure zone.